I: Biomarker quantification in fish exposed to crude oil as input to species sensitivity distributions and threshold values for environmental monitoring. (April 2017) - Sanni, Steinar; Björkblom, Carina; Jonsson, Henrik; Godal, Brit F.; Liewenborg, Birgitta; Lyng, Emily; Pampanin, Daniela M.
Abstract: The aim of this study was to determine a suitable set of biomarker based methods for environmental monitoring in sub-arctic and temperate offshore areas using scientific knowledge on the sensitivity of fish species to dispersed crude oil. Threshold values for environmental monitoring and risk assessment were obtained based on a quantitative comparison of biomarker responses. Turbot, halibut, salmon and sprat were exposed for up to 8 weeks to five different sub-lethal concentrations of dispersed crude oil. Biomarkers assessing PAH metabolites, oxidative stress, detoxification system I activity, genotoxicity, immunotoxicity, endocrine disruption, general cellular stress and histological changes were measured. Results showed that PAH metabolites, CYP1A/EROD, DNA adducts and histopathology rendered the most robust results across the different fish species, both in terms of sensitivity and dose-responsiveness. The reported results contributed to forming links between biomonitoring and risk assessment procedures by using biomarker species sensitivity distributions. Highlights: Five different species exposed to sub-lethal concentrations of dispersed crude oil. Biomarker threshold values for environmental monitoring and ERA. Selection of biomarkers that can be used to the establishment of biomarker based SSDs. Responsive biomarkers showed dose dependant response (LOEC value determination). LOEC values will contribution to the establishment of biomarker based SSDs.